2022
DOI: 10.1088/1741-2552/ac5b94
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel power electronics and magnetic nanoparticles for selective thermal magnetogenetics

Abstract: Objective. We present a combination of a power electronics system and magnetic nanoparticles that enable frequency-multiplexed magnetothermal-neurostimulation with rapid channel switching between three independent channels spanning a wide frequency range. Approach. The electronics system generates alternating magnetic field spanning 50 kHz to 5 MHz in the same coil by combining silicon (Si) and gallium-nitride (GaN) transistors to resolve the high spread of coil impedance and current required throughout the w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The small size, large surface, and more active area account for the extensive use of NPs in various applications, such as in drug delivery [ 88 ], diagnostics [ 89 ], food science [ 90 ], electronics [ 91 ], and several other biological and nonbiological areas. With the increased interest in nanotechnology in the last decade, the safety of NPs in the environment has also been considered.…”
Section: Application Of Nps In Vector-insectsmentioning
confidence: 99%
“…The small size, large surface, and more active area account for the extensive use of NPs in various applications, such as in drug delivery [ 88 ], diagnostics [ 89 ], food science [ 90 ], electronics [ 91 ], and several other biological and nonbiological areas. With the increased interest in nanotechnology in the last decade, the safety of NPs in the environment has also been considered.…”
Section: Application Of Nps In Vector-insectsmentioning
confidence: 99%
“…The force (torque) exhibited by MNPs in a uniform magnetic field can be harnessed to remotely change protein conformation, control organelles, and cells (Cho et al, 2012; Etoc et al, 2015; Hu et al, 2013; Jin et al, 2019; J. W. Kim et al, 2017). For example, superparamagnetic nanoparticles subjected to a rotating magnetic field can generate mechanical forces with a low piconewton (pN) range that can promote a conformational change of mechanosensitive ion channels and induce Ca 2+ influx into neurons for neuromodulation (Collier et al, 2022; Seo et al, 2016; Su et al, 2022; B. Wang et al, 2022; X. Wang et al, 2022). Others have also showed that magnetic nanorings can generate a mechanical force under a low‐frequency magnetic field, which can overcome the frictional force and provide the expected diffusion effect in tumor tissue.…”
Section: Mnms and Their Magneto‐responsive Propertiesmentioning
confidence: 99%
“…Using freely moving flies, the researchers showed that remote magneto‐thermal activation of TRPA1‐A channel caused a sub‐second wing‐opening response (Figure 3e,f). The introduction of novel heat‐sensitive ion channel such as TRPA1‐A was demonstrated as a good strategy to bring magneto‐thermal neuromodulation closer to the temporal precision of optogenetic methods (B. Wang et al, 2022; X. Wang et al, 2022).…”
Section: Mnms‐mediated Neuromodulationmentioning
confidence: 99%
“…A driver system was built high-electron-mobility gallium-nitride transistors (GS61008T,GaN Systems) as the H-bridge stage with an optimized magnetic board layout for high frequency and power switching operations 47 . This magnetic field driver was controlled using a custom script through Waveforms where control signals were sent through an Analog Discovery Pro (ADP3450/ADP3250).…”
Section: Magnetic Field Transmittermentioning
confidence: 99%